Probing the potential of water chestnut powder (Trapa bispinosa) in improving the shelf life of buttermilk - Rao, Sadia Rehman; Gulzar, Nabila; Nadeem, Muhammad; Rafiq, Saima; Khanum, Fakhara; Murtaza, Shamas; Ajmal, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Buttermilk, a valuable by-product of butter production, faces challenges in commercialization due to its limited shelf life and susceptibility to fungal growth. This study aimed to explore the use of water chestnut powder (WCP) as a means to extend the shelf life of buttermilk. The investigation involved evaluating the physicochemical properties, antioxidant activity, antifungal properties, and stabilizing effects of WCP in buttermilk. Buttermilk samples were prepared with varying concentrations of WCP (0%, 0.5%, 1%, 1.5%, and 2%) and stored at 4 °C for one month. The analysis of physicochemical properties showed that the concentration of WCP had a significant impact on the protein percentage, ash content, pH, and acidity of the Water Chestnut Buttermilk (WCBM). Assessment of antioxidant activity using the phosphomolybdenum method showed that, on the 21st day of storage, WCBM3 and WCBM4 exhibited total antioxidant capacities of 0.57±0.12 and 0.60±0.32, respectively, compared to the control with a capacity of 0.48±0.07. The antifungal activity of water chestnut powder buttermilk was evaluated using a qualitative method, which demonstrated inhibition of fungal growth. In the control and WCBM1 and WCBM2 treatments, the observed inhibition ranged from 1-4 mm. However, as the concentration of water chestnut powder increased in WCBM3 and WCBM4, the level of inhibition also increased. Textural analysis further indicated the stabilizing effect of WCP on buttermilk. Overall, the incorporation of WCP in buttermilk yielded promising results in terms of enhancing its physicochemical properties, antioxidant activity, antifungal potential, and textural stability. This study highlights the potential of water chestnut as an ingredient to improve the shelf life and quality of buttermilk, creating opportunities for its commercial utilization in the dairy industry.